2021
DOI: 10.3390/nu13020457
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Progress from Policy Development to Implementation: A Case Study on Adoption of Mandatory Regulation for Nutrition Labelling in Malaysia

Abstract: Mandatory nutrition labelling, introduced in Malaysia in 2003, received a “medium implementation” rating from public health experts when previously benchmarked against international best practices by our group. The rating prompted this qualitative case study to explore barriers and facilitators during the policy process. Methods incorporated semi-structured interviews supplemented with cited documents and historical mapping of local and international directions up to 2017. Case participants held senior positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Finally, the ability to explore or further implement front of pack labelling for Na in Mongolia and Malaysia, respectively, was limited by lack of back-of pack labelling of Na content. In Malaysia, a subsequent study identified further barriers such as lack of resources, governance complexity, industry resistance and lack of monitoring to regulations for nutrition labelling more broadly ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the ability to explore or further implement front of pack labelling for Na in Mongolia and Malaysia, respectively, was limited by lack of back-of pack labelling of Na content. In Malaysia, a subsequent study identified further barriers such as lack of resources, governance complexity, industry resistance and lack of monitoring to regulations for nutrition labelling more broadly ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…To address the increasing reach and impact of UCI, therefore, findings from this review suggest a need for governments to use frameworks building out from, but more comprehensive than those currently available. 2 , 22 - 27 …”
Section: Discussionmentioning
confidence: 99%
“…21 Evidence indicates that a strong regulatory framework, including monitoring, is needed to mitigate the negative health impacts of corporations. 2 , 22 - 27 There is also evidence that monitoring and accountability systems could better facilitate public health and private sector engagement on NCDs by ensuring safeguards are in place to define engagement and manage potential conflicts of interest. 25 Despite this, systematic monitoring of unhealthy corporate influence on health is largely absent at a national government level, and there is no established framework of surveillance that can be used across industries to monitor and evaluate these impacts.…”
Section: Rationalementioning
confidence: 99%
“…‘Stakeholder relations’ posed a critical barrier to both policy development and implementation, which we identified in this case study but not prevalent in the previous studies relating to food marketing policies [ 36 , 37 , 85 ]. Another case study covering mandatory nutrition labelling in Malaysia, also identified ‘stakeholder relations’ as a barrier [ 33 ]. Therefore, with reference to Malaysia, systemic influences to progress local policy reforms are required to halt inherent policy inertia.…”
Section: Discussionmentioning
confidence: 99%
“…This framework comprised key components of the Advocacy Coalition Framework [ 29 ], the Model of Agenda Building [ 30 ] and the Theory of Coalition Structuring [ 31 , 32 ]. The interview guide has been described in another case study [ 33 ] and included as Supplementary Material S1 .…”
Section: Methodsmentioning
confidence: 99%